2014
DOI: 10.4012/dmj.2013-216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver ion coating of fixed orthodontic retainers on the growth of oral pathogenic bacteria

Abstract: Titanium and stainless steel wires used for retainers in orthodontic procedures were coated with Ag ions and the effects of the coating on common oral pathogens and their pathogenicity were investigated. Two species of cariogenic and three species of periodontopathic bacteria were assessed. Biofilms of Streptococcus sobrinus and two VSC gases produced by P. gingivalis were also examined. Ag ioncoated wires showed marked antibacterial activities compared with uncoated wires; in most cases, the differences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
2
29
0
2
Order By: Relevance
“…Consequently, they suggested that this was due to the decreased accumulation of silver ions in bacteria cells. 19 In the present study, Gramnegative bacteria were more susceptible to silver ions, which was in agreement with the results of other researchers. 50,51 The higher activity of SNPs against Gram-negative bacteria was …”
supporting
confidence: 83%
See 4 more Smart Citations
“…Consequently, they suggested that this was due to the decreased accumulation of silver ions in bacteria cells. 19 In the present study, Gramnegative bacteria were more susceptible to silver ions, which was in agreement with the results of other researchers. 50,51 The higher activity of SNPs against Gram-negative bacteria was …”
supporting
confidence: 83%
“…These results were in agreement with those from the study by Morita et al, where the concentration of 0.043 ppm sufficiently inhibited oral streptococci and P. gingivalis. 19 In this study, P. gingivalis, E. coli, and S. aureus appeared the most susceptible to SNPs. Oral streptococci were the least susceptible to nanosilver, with S. mutans being the most resistant, but the overall differences …”
mentioning
confidence: 99%
See 3 more Smart Citations